2008
DOI: 10.2215/cjn.03690907
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Induced Nephropathy

Abstract: Background and objectives:Observational studies have demonstrated that short-and long-term mortality is increased in patients who develop contrast-induced nephropathy (CIN). The more clinically relevant questions, and the objectives of this review, are whether CIN is causally related to mortality, and to what extent could mortality in patients undergoing contrast procedures be reduced by preventing CIN.Design, setting, participants, & measurements: A literature review was conducted, focusing on observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 20 publications
4
120
1
3
Order By: Relevance
“…1 Although, mostly, there are no permanent sequelae of radiocontrast nephropathy (RCN), its development may be associated with bad consequences. 2 The best way to avoid these consequences is to prevent RCN. A variety of preventive measures may reduce the risk.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although, mostly, there are no permanent sequelae of radiocontrast nephropathy (RCN), its development may be associated with bad consequences. 2 The best way to avoid these consequences is to prevent RCN. A variety of preventive measures may reduce the risk.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicated that CIN occurs in 4 to 20% of patients after intra-arterial administration after coronary angiography [13,14]. Many patients who undergo formal angiography including coronary angiography are admitted in the hospitals, causing a different physiologic status than ambulatory patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of development of CIN are not completely understood yet. 3,4 Despite the observation that diabetic patients undergoing PCI are at an increased risk for developing CIN, no definite pharmacological therapy has been defined for preventive practice. Thus, the identification of patients who are at an enhanced risk of development of CIN is pertinent.…”
Section: Original Articlementioning
confidence: 99%